Treatment of Odontoid Fractures: Recommendations of the Spine Section of the German Society for Orthopaedics and Trauma (DGOU) - Gonschorek, Oliver (Global Spine J, 2018)
STUDY DESIGN: Narrative review. OBJECTIVE: To establish recommendations for the treatment of odontoid fractures based on current literature and the knowledge of the experts of the Spine Section of the German Society for Orthopaedics and Trauma (DGOU). METHODS: Narrative review of the literature. Analyzing treatment algorithms of German trauma and spine centers as members of the Spine Section of the German Society for Orthopaedics and Trauma (DGOU). RESULTS: There are many influencing factors leading to appropriate treatment of odontoid fractures such as age, bone quality, arthrosis, classification, and type of the fracture. Conservative nonoperative treatment is appropriate for stable undislocated displaced odontoid fractures. Anterior osteosynthesis with 1 or 2 screws leads to good results in the classical unstable type II odontoid fracture in patients with good bone quality. However, modifiers have been identified by the working group leading to higher complication and failure rates. For these cases, more stable constructs and/or posterior approaches are indicated. CONCLUSIONS: Operation seems to be standard treatment for odontoid fractures. However, in the aged population, conservative treatment should be considered as morbidity and mortality rise significantly in the group of >75 years. Conservative treatment may also be started within stable nondislocated fractures, but then regular controls have to be performed. If operation is indicated, many influencing factors have to be considered for appropriate approach and technique. The classification of Anderson and D’Alonzo is still standard. To create an adequate treatment algorithm, dislocation displacement and instability have to be identified. Stable odontoid fractures are treated conservatively non-operatively, but if so regular controls have to be performed. Unstable and/or dislocated displaced odontoid fractures are treated by anterior osteosynthesis with 1 or 2 screws. The technique is demanding and leads to elevated complication and failure rates if modifiers are apparent. In these cases, posterior instrumentation or fusion of C1 and C2 is favorable. In the aged population (>80 years), operative therapy is critical as postoperative morbidity complication and mortality rates rise significantly. As there is still some bias in the treatment algorithms, the working group recommends establishment of a prospective study to result in more objective statements.